The use of High-Flow Nasal Oxygen Therapy in 4 dogs undergoing bronchoscopy - de Jaureguizar Tesas, Maria Rosa; Matson, Hannah; Tappin, Simon; Thomas, Emily (Frontiers in Veterinary Science, 2023)
Introduction High-Flow Nasal Oxygen Therapy is a method to deliver warmed, humidified air-oxygen blended at high flow rates to patients through a nasal cannula using a specialized, commercially available machine. This is a well-tolerated, safe and effective method for oxygen delivery to healthy and hypoxemic dogs. Patients undergoing bronchoscopic procedures frequently develop hypoxemia. Human trials have shown a reduction in incidents of hypoxemic events and higher pulse oximeter oxygen saturation during bronchoscopies in patients on High-Flow Nasal Oxygen. Materials and methods This is a single-centre, prospective case series. All dogs weighing between 5 and 15 kg and undergoing bronchoscopy during the study period (03/07/2022-01/10/2022) were eligible. Results Twelve patients were eligible for inclusion of which four were enrolled. No clinically significant complications related to the use of High-Flow Nasal Oxygen Therapy were recorded. Two of the patients were re-intubated post bronchoscopy due to clinician preference for recovery. One of the patients had a self-limiting period of severe hypoxemia with a pulse oximeter oxygen saturation of 84% for < 1 min during bronchoalveolar lavage, and whilst undergoing High-Flow Nasal Oxygen administration. Another patient had a self-limiting episode of mild hypoxemia (SpO2 of 94% lasting < 1 min) 5 min after completion of bronchoalveolar lavage. Conclusion No clinically relevant complications relating to High-Flow Nasal Oxygen Therapy were recorded in this case series, although further studies are required to confirm this conclusion. This initial data suggests that the use of High-Flow Nasal Oxygen therapy during bronchoscopy is feasible and potentially safe, although it may not prevent hypoxemia in these patients. The use of High-Flow Nasal Oxygen Therapy during bronchoscopy in small patients carries multiple potential benefits and further studies to compare its efficacy against other traditional oxygen delivery systems are warranted in this patient population.